Maternal self-care practices in a rural community in Sultan Kudarat province - Sarmiento, June Pearl D. (Animo Repository, 2014)
This study describes the maternal self-care practices of 20 mothers in rural community in Sultan Kudarat Province. This also intends to determine their perception of their health status as well as the variations in their self-care practices in terms of their background characteristics and their participation in health programs available in the community. This exploratory study made use of qualitative method of in-depth interview. Mothers have holistic maternal self-care practices: physical, psychosocial, spiritual, cultural and clinical self-care practices. Variation in maternal self-care practices is influenced by age, engagement in livelihood activities, household headship and sources of help and participation in health programs. Mothers who are young, with multiple livelihood activities, head of household and with sources of immediate help have varied psychosocial self-care activities. Also, mothers who participated in health programs with psychosocial health related topics are more inclined to practice self-care. Majority of the mothers have positive perception of their health status after they perform certain self-care activities. This study suggest that health related programs in the community can provide one avenue for mothers to take more control over their own health and own time.